2022
DOI: 10.1155/2022/2233484
|View full text |Cite
|
Sign up to set email alerts
|

Centralization and Firm Performance: New Evidence on the Role of Firm Size

Abstract: Centralization has been regarded as an important factor in corporate governance in the academic and business communities. Although several studies have examined the relationship between centralization and firm performance, the conclusions remain mixed. We extend existing research by introducing firm size as a threshold variable into our model to explicate the complicated effects of centralization on firm performance. We found that a high degree of centralization can promote firm performance significantly in sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the studies about firm size, on one hand, Kuncová et al ( 56 ), Ibhagui & Olokoyo ( 57 ) and Mubeen et al ( 58 ) found that large firms outperformed small firms in profitability, and firm size can positively moderate the relationship between factors such as financial leverage, product market competition and firm investment performance. On the other hand, Dhawan ( 59 ) and Fan’s et al ( 60 ) studies found that firm size is negatively correlated with company performance. Similarly, there may also be a positive or negative relationship between financial leverage and profitability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…In the studies about firm size, on one hand, Kuncová et al ( 56 ), Ibhagui & Olokoyo ( 57 ) and Mubeen et al ( 58 ) found that large firms outperformed small firms in profitability, and firm size can positively moderate the relationship between factors such as financial leverage, product market competition and firm investment performance. On the other hand, Dhawan ( 59 ) and Fan’s et al ( 60 ) studies found that firm size is negatively correlated with company performance. Similarly, there may also be a positive or negative relationship between financial leverage and profitability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…is issue also connects with the problem of the use of qualitative variables, which have been largely ignored in many studies on business quality [152,153] and which could provide a good explanation about the endurance of the firms over time. e uncertainty, the instability of certain states, the capacity of dynamism and innovation, the complexity of the governance structure, or the competition degree are factors considered in the eory of Business Organisation [154][155][156][157] as these factors have implications in the longevity of the companies and should yet be modelled in integrated studies. Table 1 summarises all the main explanatory approaches to the business survival theories in the literature, and the most representative papers in each case.…”
Section: Introductionmentioning
confidence: 99%